2006
DOI: 10.1074/jbc.m600943200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Engagement of Modules 1 and 4 of Vascular Cell Adhesion Molecule-1 (CD106) by Integrins α4β1 (CD49d/29) and αMβ2 (CD11b/18) of Eosinophils

Abstract: We have studied adhesion of eosinophils to various forms of vascular cell adhesion molecule 1 (VCAM-1, CD106), an integrin counter-receptor implicated in eosinophil recruitment to the airway in asthma. Full-length 7d-VCAM-1, with seven immunoglobulin-like modules, contains integrin-binding sites in modules 1 and 4. The alternatively spliced six-module protein, 6d-VCAM-1, lacks module 4. In static assays, unactivated purified human blood eosinophils adhered similarly to recombinant soluble human 6d-VCAM-1 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 85 publications
(35 reference statements)
2
63
0
1
Order By: Relevance
“…Several mechanisms which may predispose GERD patients for the development of EoE have been described, such as acid peptic damage to the tight junctions between epithelial cells affecting permeability of the esophageal epithelium for allergens (27,28), as well as enhancement of expression of adhesion molecules and production of inflammatory mediators and cytokines that attract and recruit inflammatory cells including eosinophils in the esophagus (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms which may predispose GERD patients for the development of EoE have been described, such as acid peptic damage to the tight junctions between epithelial cells affecting permeability of the esophageal epithelium for allergens (27,28), as well as enhancement of expression of adhesion molecules and production of inflammatory mediators and cytokines that attract and recruit inflammatory cells including eosinophils in the esophagus (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…␣ M ␤ 2 is believed to be important for eosinophil migration (22,51,53,(93)(94)(95). Thus, the scenario has migrating eosinophils using activated ␣ M ␤ 2 and possibly other integrins to interact with multiple substrates (22,36,92), including VCAM-1, ICAM-1, and extracellular matrix proteins, on endothelial cells, in connective tissue, and on epithelium of the bronchial wall. …”
Section: Discussionmentioning
confidence: 99%
“…Circulating eosinophils with activated ␤ 1 and up-regulated ␣ D are presumed to have a higher probability of arresting on VCAM-1 on the activated endothelium of the bronchial circulation (Fig. 11), because adhesion of purified blood eosinophils to VCAM-1 is mediated by ␣ 4 ␤ 1 (22,92), with a possible contribution by ␣ D ␤ 2 (22,31). ␣ M and␤ 2 are shown as being up-regulated and ␤ 2 integrins as being activated by IL-5, also elaborated in response to allergen.…”
Section: Discussionmentioning
confidence: 99%
“…Halfon S and colleagues (10) showed that only 16.7% of fibroblasts expressed ITGA11 on their surface compared with MSCs of early (51.4%) and late (28.6%) passages. CD106 (also known as vascular cell adhesion molecule-1 VCAM-1) is a member of the Ig superfamily which mediates leukocyte-endothelial cell adhesion and signal transduction during inflammation (13,14). It was shown that CD106 protein was expressed only on MSCs but not on fibroblasts (10).…”
Section: Differences Between Mesenchymal Stem Cells and Fibroblastsmentioning
confidence: 99%